Desain Generator Magnet Permanen Sebagai Pembangkit Listrik Tenaga Angin Pada Daerah Kecepatan Angin Rendah - Wuryanduri, Rehang (2016)
This research aims at designing and creating a permanently magnetic generator with low speed, whichlater can be used as a wind electric generator in Indonesian territory, for which commonly wind rapidity in Indonesia is included to an under pace type. This research method is to design and create a rotor current with neodymium permanent magnet in size of 50mm x 15mm x 6mm, in this generator two kinds of rotors have been used in which it has 12 permanent magnets in each. The next one is to design and create a stator, a stator has 10 types of poles and it has 720 coils with an email wire diameter of 0,8mm. This generator has been examined in electrical engineering laboratory of UMS in 31th December 2015 with an AC 1 motor as an activator. This generator has been examined with the amount of 100-500 RPM circles with an accumulator as the load. The result of this research provides an information that adding a rotor can increase two times higher of voltage output. In the circle of 100 RPM, this generator has been proved to be able to make an admission filling to the accumulator with an output of 0,13 A DC, whilst in 500 circle, it has been able to do a filling of a current of 0,72 A DC. The results of the voltage output have been changed into DC and given IC regulator LM7815. Therefore the voltage used to make an admission filling to the accumulator could be stable